A relação entre renda e composição domiciliar dos idosos no Brasil: um estudo sobre o impacto do recebimento do Benefício de Prestação Continuada - Maira Andrade Paulo (2008)
This work investigates the relationship between an elderlys income and their living arrangements. Two hypotheses are raised in the literature about the impact of the elderlys income on their living arrangements. On the one hand, receiving an income can motivate the elderly to look for privacy and independence while opting for an independent living arrangement. On the other hand, the income received by the elderly can attract family members whose aim is to gain advantage from that income. This discussion is relevant in the current Brazilian context, which has been marked by rapid population ageing, deep changes in living arrangements and an expansion of Social Security for the elderly. In order to clarify the aforementioned relationship, this work investigates the impact of the Continuous Cash Transfer (BPC) on the elderlys living arrangements. This benefit corresponds to an income received monthly, which is worth one minimum salary, by the elderly over 65 years old, whose per capita income is lower than a quarter of a minimum salary. The proposal is to verify whether a BPC additional income would lead the elderly to look for the establishment of an independent household or whether that income would instead attract their family members to stay around in order to profit from it, due mainly to the poverty status affecting those individuals. To answer this question, the difference-in-difference statistical method was used in addition to 2002 and 2004 PNAD data. The result obtained shows that receiving the extra BPC income increases the probability that the elderly will choose to live alone.